(untitled) (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2026)
The review proposes a reading of Crimes of the Future (David Cronenberg, 2022), taking the body as a field of political and sensory dispute. By following Saul Tenser’s trajectory and the emergence of new forms of organic art, the text discusses the clash between the obsolescence of the human body in the face of normative projects of the future and the bodily imaginations that emerge from ecological paradigms, articulating body, nature, technique, and political imagination. Keywords: David Cronenberg; Anthropocene; Political Imagination; Body; Aesthetics.